ERdj5 in Innate Immune Cells Is a Crucial Factor for the Mucosal Adjuvanticity of Cholera Toxin - Kim, Mee-Sun; Yi, Eun-Je; Kim, Young-In; Kim, So Hee; Jung, Yi-Sook; Kim, Seong-Ryeol; Iwawaki, Takao; Ko, Hyun-Jeong; Chang, Sun-Young (Frontiers in Immunology, 2019)
Cholera toxin (CT) is one of most strong mucosal adjuvants, but it cannot be clinically used owing to its toxicity. The cytosolic A1 subunit of CT (CTA1) is the molecule responsible for its immunostimulatory activity, which increases the concentration of cyclic AMP and causes the induction of pro-inflammatory cytokines in innate immune cells. However, the importance of endoplasmic reticulum (ER) molecules involved in CTA1 retro-translocation to induce immune responses remained to be investigated. ERdj5 is an ER protein which is expected to transfer CTA1 to the Hrd1 complex for the retro-translocation of CTA1. In this study, we investigated the physiological relevance of ERdj5 in immune stimulation by CT. ERdj5-knockout (ERdj5 KO) mice had decreased production of antigen-specific IgG in the serum and IgA in the mucosal secretion after intranasal immunization with Ag and CT. Especially, IgG2c isotypes were specifically reduced in the absence of ERdj5. ERdj5 KO dendritic cells (DCs) failed to full activation with decreased expression of costimulatory molecules, such as MHC class II, CD80, and CD 86. In ERdj5 KO DCs, secretion of pro-inflammatory cytokines, such as IL-1β, TNF-α, and IL-6, was reduced. The cytokine signatures of several helper T cells were reduced in ERdj5 KO mice following intranasal CT immunization. The absence of ERdj5 affects the immunostimulatory properties of CT but does not affect the response to the CTB pentamer, the response to alum, total antibody production, or cytokine release from DCs exposed to CpG. Interestingly, CT enhanced the expression of ER stress proteins in ERdj5 KO innate immune cells. These results suggested that ERdj5 contributed as a decisive factor to the immunostimulatory capacity of CT via CTA1 retro-translocation.